ROLE OF GINKGO BILOBA IN ATTENTION DEFICIT HYPERACTIVITY DISORDER (ADHD) - Syakirin, Muhammad Ilham (Journal of Psychiatry Psychology and Behavioral Research, 2025)
Introduction – Attention-deficit Hyperactivity Disorder (ADHD) is a chronic, neurological condition that happens in many children and is defined by a high level of hyperactivity, inattention, and impulsivity that is persistent and debilitating. Currently, the first-line treatment for ADHD is the use of stimulant medicines such as Methylphenidate and Amphetamine, although they have a variety of undesirable side effects, including growth retardation, addiction, and substance misuse. Ginkgo biloba is a traditional herbal medicine that has been used to treat early-stage AD, vascular dementia, and other forms of dementia in the early stages. This paper aims to evaluate the role of Ginkgo biloba as a promising alternative treatment to Attention-deficit hyperactivity disorder. Methods – The article is made by reviewing and evaluating several literatures that discusses ADHD, ginkgo biloba, and also the role and effectiveness of ginkgo biloba in managing symptoms found in patients with ADHD. The literature used is limited to articles published between 2010 – 2022. Results – Studies that were reviewed has shown that ginkgo biloba significantly improves the symptoms of patients with ADHD. The improvement is related to ADHD symptoms which is shown by the significant reduction in Parents and Teacher ADHD Rating score. Discuss – Although ginkgo biloba has shown significant advantage when compared to placebo treatment, it is still inferior compared to stimulant drugs such as methylphenidate. These improvements can be correlated to EGb761’s neuroprotective ability and some studies suggests that EGb761 improves neurotransmission particularly in glutamatergic, cholinergic, and dopaminergic systems. Conclusion – Ginkgo biloba has shown a role in managing symptoms of ADHD in children by improving the symptoms and parent and teacher ADHD rating scale. It is suggested to further evaluate the clinical efficacy, long-term safety, and dose finding of ginkgo biloba in ADHD and possibly, a combination therapy with stimulant medication in future research.